Prove that if \(a, b, c \) are non-negative real numbers such that \( a + b + c = 3 \), then we have

\[ ab^2 + bc^2 + ca^2 + abc \leq 4 . \]

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestThis is quite a famous inequality, and there are several approaches that could be taken. Here is the simplest proof that I know of.

Define \( f( a, b, c) = ab^2 + bc^2 + ca^2 + abc \). WLOG, we may assume that \( a \) is the median of the 3, IE we either have \( b \leq a \leq c \) or \( b \geq a \geq c \).

Step 1:We will show that \( f(a,b,c) \leq f ( a, b+c, 0 ) \). This approach is known as Smoothing.This follows by expanding both sides, and we want to compare \( ab^2 + bc^2 + ca^2 + abc \leq a(b+c)^2 \), which simplifies to

\[ bc^2 + ca^2 \leq abc + ac^2 \]

This is equivalent to

\[ c ( a - b ) ( a - c) \leq 0 \]

From the assumption that \(a\) is the middle number, we know that \( a-b, a-c \) will have different signs (or be 0). Since \( c \) is non-negative, hence the entire product will be \( \leq 0 \).

This is essentially how we approach @Krishna Sharma 's Case 1.

Step 2:We show that subject to \( a + b = 3 \), we have \( f(a, b, 0) \leq 4 = f ( 1, 2, 0) \).By AM-GM, we get

\[ f(a, b, 0) = ab^2 = 4 \times a \times \frac{b}{2} \times \frac{b}{2} \leq 4 \left( \frac{a + \frac{b}{2} + \frac{b}{2} } { 3} \right) ^3 = 4 .\]

Hence, the result follows.

However, I do not know of an easy way to motivate the approach, and in particular step 1. Any thoughts or comments?

Log in to reply

Sir, What is meant by IE ?

Log in to reply

It's just another way to write i.e. which means "that is".

Log in to reply

Minor typo in the last step where you use AM-GM.

\[4\times a\times \left(\frac{b}{2}\right)^2\leq 4\left(\frac{a+\frac{b}{2}+\frac{b}{2}}{\color{red}{3}}\right)^3=4\]

Log in to reply

Thanks fixed.

Log in to reply

This is just a comment, not a solution.I remember seeing a stronger version of this inequality somewhere recently (probably on Math SE) which stated the following:

Our required inequality trivially follows from the stated inequality. However, proving the said

strongerinequality seems to be harder than I expected. Let me see if I can think of a proof to that. For the time being, others are welcome to post their proof (if any) for the statedstrongerinequality.Log in to reply

Note that the inequalities are equivalent. What happened was that we

normalizedthe inequality, meaning that we made all of the terms have the same polynomial degree. To do so, we multiplied, where necessary, by \( a + b + c = 3 \).This is a standard approach, and one that I would often (though not always) recommend to use if the terms have different degrees.

The weaker version that you saw, was most likely

\[ ab^2 + bc^2 + ca^2 \leq 4 \Leftrightarrow ab^2 + bc^2 + ca^2 \leq \frac{4}{27} ( a + b + c ) ^ 3 . \]

Log in to reply

Let \[f(a,b,c)=ab^2+bc^2+ca^2+abc + k(a+b+c-3)\] (say this as equation \((1)\)

Solving these four equations \[\frac{\partial f}{\partial a} = 0\] \[\frac{\partial f}{\partial b} = 0\] \[\frac{\partial f}{\partial c} = 0\] \[a+b+c=3\]

we get \[a=b=c=1 , k=-4\]

substituting this back in equation \(1\) , we get \[f_{max}(a,b,c)=1+1+1+1-4(0) = 4\]

\(\textbf{Q.E.D}\)

@Calvin Lin sir

Log in to reply

This demonstrates the point of this problem.

You did not perform the Lagrangian properly. At the IMO, this solution will be scored 0/7.

1. You did not state the equations.

2. You did not state how to solve the equations.

3. You missed out the equality case of \( (1, 2, 0) \).

Log in to reply

I didn't miss the case 1,2,0 doesnt satisfy the third equation ,i.e. , df/dc = 0

Log in to reply

boundary condition. IE You didn't perform the Lagrangian properly.E.g. What is the maximum of \( f(x) = x^2 \) on the interval \( [-2, 2] \)? Do you say that " \(f' = 0 \Rightarrow x = 0 \) hence the maximum is \( f(0) = 0 \)? No, we still have to check the boundary points, where they need not satisfy \( f' = 0 \) in order to be a maximum on the restricted domain.

Log in to reply

Log in to reply

For example, if you ignore the boundary condition when calculating the max of \( f( x) = x^2 \) on the closed interval \( [1, -1] \), then you would not get any answer.

Log in to reply

ok i will keep in mind always to check at boundary

Log in to reply

This problem becomes quite a standard exercise when you use Lagrange multipliers. I think that the challenge is to prove the given inequality without using that which would be the reason for the problem being tagged under Algebra.

Log in to reply

i dont think so ... :)

Log in to reply

On the other hand, you need to show that the extremal point you've found is a global maximum point as opposed to an inflection point or a global minimum point.

Log in to reply

Comment deleted Apr 22, 2015

Log in to reply

Case 1 doesn't work. When you calculated \( \frac{a}{b} + \frac{b}{c} + \frac{c}{a} \geq 3 \), you found the minimum of the expression, but we want the maximum of the expression.

Also, you cannot "Say we want to maximize \( fg \), then we maximize \(g\) and see what happens". This is what you are doing by saying "the maximum of \(abc\) occurs at \(a = b = c = 1 \)". In particular, when \( a = 2, b = 0.1 \), note that the expression \( f \geq 20 \), and so you have to explain how to compensate for that.

For case 2, your equality case is \( a + b = 3, a = \frac{b}{2} \), yielding \( (1,2,0) \). I'm not sure why you listed \( (2,1,0 ) \).

Log in to reply

Comment deleted Apr 20, 2015

Log in to reply

Saying "apply Lagrange Multiplier" is a cop-out, unless you actually work through the details.

In the IMO, the above proof would be worth 0.

Log in to reply

Comment deleted Apr 20, 2015

Log in to reply

It is not trivial to show that "..." obtain their maximium value at \( a = b = c = 1 \). In fact, none of them do. For example, take \( a = b = 1.5 \) in any of these, and we obtain a higher value.

Note: Given that the equality conditions are \( (1,1,1), (1,2,0), (0,1,2), (2,0,1) \), it is hard for any of the "classical inequalities" to be applied in a direct manner.

Log in to reply

Is some info missing? Because substituting \(a=b=c = \frac{4}{3}\) yields a value around 9.5

Log in to reply

Ooops, the condition should have been \( a+b+ c = 3 \).

Log in to reply

Why not assume a=b= c=1 and do it

Log in to reply

Myth: An expression attains it's maximum or minimum when all (some) of the variables are equal.

Log in to reply